Pengaruh Konten Media Sosial Instagram dan Frekuensi Iklan Podcast Terhadap Brand Awareness pada Produk Teh Botol Sosro di Kota Binjai (Studi pada Konsumen Produk Teh Botol Sosro di Kota Binjai): Penelitian - Nurmailiza; Nicholas Marpaung (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Brand awareness is the extent to which consumers recognize and remember a brand. Teh Botol Sosro strives to increase brand awareness through Instagram social media content and frequent podcast advertising to reach consumers in Binjai City. However, complaints remain regarding a lack of consumer knowledge regarding these promotions. This study aims to analyze the influence of Instagram social media content and podcast advertising frequency on Teh Botol Sosro brand awareness, both partially and simultaneously. The method used is quantitative research with an associative approach. Primary data was obtained through questionnaires from 100 respondents using purposive sampling, while secondary data came from literature and previous research. Analysis was conducted using instrument testing, classical assumption testing, multiple linear regression, and regression model testing. The results indicate that Instagram social media content has a positive and significant effect on brand awareness, with a tvalue of 5.214 > 1.984, a significance level of 0.000 < 0.05, and a positive regression coefficient of 0.301. The frequency of podcast advertising also has a positive and significant effect on brand awareness, with a tvalue of 5.764 > 1.984, a significance of 0.000 < 0.05, and a positive regression coefficient of 0.453. Simultaneously, both variables have a significant effect on brand awareness with an Fvalue of 53.505 > 3.09 and a significance of 0.000 < 0.05. The magnitude of the influence is 52.5%, while the remaining 47.5% is influenced by other factors outside the study.